Reformulasi Sanksi Tindak Pidana Perzinaan Dalam Pembaharuan Hukum Pidana Indonesia - Syawitri, Dissa Mutiara; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 248 of the Criminal Code has a very low sentence. Is an action that can be done by a man orwoman, one of whom is married and is a complaint offense that can only be complained of by the victim'shusband or wife. Most of the revisions to the adultery article were against the approved conviction and wereagainst the community. Article 284 imprisonment is only nine months imprisonment in article 484 the PenalCode draft is five years in prison. With a low sentence makes the perpetrators of criminal acts do not use adeterrent and this adultery article rarely appears while the impact of adultery can lead to crimes such asabortion, domestic violence, and the impact of hernia. The purpose of discussing this thesis, namely; First,To Understand Lawsuits in Indonesia. Second, to find out the renewal of criminal sanctions for adultery inthe renewal of Indonesian law.This type of research used in this legal research is normative juridical method, this research isdescriptive, which is a study that discusses the topics described and detailed. Source of data used secondarydata and tertiary legal materials. The technique of collecting data in this study is the literature reviewmethod after the data collected is then analyzed to draw conclusions.From the results of research and discussion it can be concluded that, First, the act of adultery hasreleased norms / values of decency and is in conflict with all religions in Indonesia. Second, let us discussthe follow-up of adultery which can be adjusted to the development of the community and their respectiveregions so that it does not occur due to criminalization.Keywords: Reformulation-Sanctions-Adultery-Criminal Law